2018
DOI: 10.1038/s41593-018-0075-7
|View full text |Cite|
|
Sign up to set email alerts
|

Striatal neurons directly converted from Huntington’s disease patient fibroblasts recapitulate age-associated disease phenotypes

Abstract: In Huntington’s disease (HD), expansion of CAG codons within the huntingtin gene (HTT) leads to the aberrant formation of protein aggregates and the differential degeneration of striatal medium spiny neurons (MSNs). Modeling HD using patient-specific MSNs has been challenging, as neurons differentiated from induced pluripotent stem cells are free of aggregates and lack an overt cell death phenotype. Here we generated MSNs from HD patient fibroblasts through microRNA-based neuronal conversion, previously shown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
247
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 209 publications
(256 citation statements)
references
References 47 publications
(75 reference statements)
9
247
0
Order By: Relevance
“…Tang et al [157] have generated induced motor neurons, as well as iPSC-derived motor neurons from three young (0-3 years) and three old (53-71 years) healthy donors, as well as from four familial ALS patients carrying SOD1 or FUS mutations. In consistence with the observation that HD iPSC-derived neurons need external stressors to display this disease phenotype, the authors showed that an age-related collapse in proteostasis triggered huntingtin aggregation in an age-and repeat-lengthdependent manner [7]. While this study did not assess any age-related differences between patientand control-derived induced motor neurons, an impressive study by Victor et al [7] demonstrated the importance of modeling old age as a disease-relevant factor in a model consisting of both iPSC-derived and fibroblast-derived medium spiny iNs.…”
Section: You Are What You Eat: Metabolic Hallmarks Of In Conversionmentioning
confidence: 77%
See 2 more Smart Citations
“…Tang et al [157] have generated induced motor neurons, as well as iPSC-derived motor neurons from three young (0-3 years) and three old (53-71 years) healthy donors, as well as from four familial ALS patients carrying SOD1 or FUS mutations. In consistence with the observation that HD iPSC-derived neurons need external stressors to display this disease phenotype, the authors showed that an age-related collapse in proteostasis triggered huntingtin aggregation in an age-and repeat-lengthdependent manner [7]. While this study did not assess any age-related differences between patientand control-derived induced motor neurons, an impressive study by Victor et al [7] demonstrated the importance of modeling old age as a disease-relevant factor in a model consisting of both iPSC-derived and fibroblast-derived medium spiny iNs.…”
Section: You Are What You Eat: Metabolic Hallmarks Of In Conversionmentioning
confidence: 77%
“…Interestingly, only 30 years later and a few years after the invention of induced pluripotent stem cells (iPSCs) [5], the direct conversion of fibroblasts into induced neurons (iNs) was discovered [6]. From this point onward, direct conversion technologies have grown rapidly, and are today mostly regarded as a subdiscipline of the stem cell field, where they are seen as alternative approaches to generate cell types of interest from human patients and donors for disease modeling or regenerative purposes [7,8]. From this point onward, direct conversion technologies have grown rapidly, and are today mostly regarded as a subdiscipline of the stem cell field, where they are seen as alternative approaches to generate cell types of interest from human patients and donors for disease modeling or regenerative purposes [7,8].…”
Section: Why We Need Human Neurons In a Dishmentioning
confidence: 99%
See 1 more Smart Citation
“…Although neurons generated from Huntington's disease patient-derived iPSCs showed no HTT aggregates, or only when treated with proteasome inhibitors, iN cells exhibited HTT aggregates [61]. Although neurons generated from Huntington's disease patient-derived iPSCs showed no HTT aggregates, or only when treated with proteasome inhibitors, iN cells exhibited HTT aggregates [61].…”
Section: Direct Reprogramming Preserves Aging Hallmarksmentioning
confidence: 98%
“…To overcome this limitation, different combinations of genetic factors have been used to allow direct fate conversion of human fibroblast to neurons and production of neurons that maintain age‐associated epigenetic marks (Huh et al, ). Lineage reprogramming has been used for the generation of striatal and motor neurons to gain novel insights into Huntington's disease and ALS (Tang et al, ; Victor et al, ).…”
mentioning
confidence: 99%